High Prevalence of Colistin-Resistant Escherichia coli with Chromosomally Carried mcr-1 in Healthy Residents in Vietnam - Takahiro Yamaguchi (American Society for Microbiology, 2020)
ABSTRACT The wide distribution of colistin-resistant bacteria in developing countries has become a common phenomenon. To understand the mechanisms underlying their distribution, we studied the mcr genetic background of colistin-resistant Escherichia coli isolates from the fecal microbiota of healthy human residents from a community in Vietnam with a high prevalence of colistin-resistant E. coli with mcr. Fifty-seven colistin-resistant isolates were obtained from 98 residents; one isolate was collected from each individual and analyzed for mcr. We found that 36.8% of the isolates carried chromosomal mcr-1. Further, 63.2% and 1.8% of the isolates carried mcr-1 on the plasmid and the plasmid/chromosome, respectively. Whole-genome sequencing of genetically unrelated isolates showed that the majority (6 of 7) of the isolates had the chromosomal mcr-1 in a complete ancestral mcr-1 transposon Tn6330, ISApl1-mcr-1-PAP2-ISApl1, which was inserted at various positions on the chromosomes. In addition, the majority (87.5%) of Tn6330 of mcr-1-carrying plasmids (n = 8) lacked both upstream and downstream ISApl1 transposons. The results obtained in this study indicate that plasmid-to-chromosomal transfer of mcr-1 may have occurred recently in the fecal microbiota of the residents. Additionally, Tn6330 on the chromosome may lose ISApl1 from the transposon during multiplication to gain a more stable mcr-1 state on the chromosome. Stabilization of resistance by the chromosomal incorporation of mcr-1 would be an additional challenge in combating the dissemination of resistant bacteria. IMPORTANCE Elucidation of the mechanism of the wide dissemination of colistin-resistant bacteria in communities of developing countries is an urgent public health issue. In this study, we investigated the genetic background of the colistin resistance gene mcr in E. coli isolates from the fecal microbiota of healthy human residents living in a community in Vietnam with a high prevalence of colistin-resistant E. coli. Our study revealed for the first time, a surprisingly high percentage (36.8%) of colistin-resistant E. coli carrying chromosomal mcr-1, the emergence of which may have occurred recently, in the fecal microbiota of the community residents. The mcr-1 transposon on the chromosome may develop into a more stable genotype by the loss of insertion sequences (ISs). Our results are valuable in understanding the mechanism underlying the increasing prevalence of colistin-resistant bacteria within a community.